The Performance Evaluation Mechanism Based on Information Construction for Large Stand-Alone Medical Equipment and Its Support for Decision-Making of Purchasing - Qing LU (Tehran University of Medical Sciences, 2020)
Background: Continuously deeper reform of public hospitals has put forward the need to innovate the philosophy and system of large medical equipment operation and management, and the phenomenon featuring "more attention to purchasing and less attention to management" need to be turned around. Methods: This research took use of information management to set up ID fields (unique number) for target stand-alone equipment; integrated statistics functions of HIS, PACS, LIS, RIS and equipment management system to get the basic operation data; informationized the work flow and reform technology to set up a post evaluation indictor system for the performance of stand-alone equipment; compared the service condition of newly purchased equipment with the feasibility application of relative department from various dimensions; designed objective post-evaluation indicators from various angles to scientifically manage existing medical equipment and support decision-making of new application for purchasing medical equipment. Results: Application performance of stand-alone equipment and clinical departments were ranked in a standardized manner. Decision-making mode based on data case of stand-alone equipment was set up. Net present value was evaluated. However, re-purchasing the instrument did not continuously increase the contribution of each instrument. The laboratory can purchase new instruments again, while the imaging department is not recommended to purchase. Conclusion: The performance evaluation mechanism based on information construction for large stand-alone medical equipment and its support for decision-making of purchasing is of great significance to improve the service life of equipment, exert the maximum effect and reduce economic waste.